Diassociative algebras and their derivations - Rikhsiboev, Ikrom M.; Rakhimov, Isamiddin Sattarovich; Basri, Witriany (Institute of Physics Publishing, 2014)
The paper concerns the derivations of diassociative algebras. We introduce one important class of diassociative algebras, give simple properties of the right and left multiplication operators in diassociative algebras. Then we describe the derivations of complex diassociative algebras in dimension two and three.